PETROCHEMISTRY OF ROCKS IN THE PEGMATITE ZONE OF THE PRECAMBRIAN CENTRAL NIGERIA: AN ECONOMIC POTENTIAL PERSPECTIVE - Adeyemi, O.O.; Adebisi, N.O.; Egbeyemi, O.R. (Academy Journal of Science and Engineering)
Pegmatites occur in association with amphibolites, minor granite-gneiss and quartzites in central Nigeria. Findings on their economic potentials are yet to reveal more representative and accurate depiction of their characteristics. This paper employs both geochemical and mineralogical evaluation for ample economic potentials based on computation of analyses of low-lying dome shaped hills of granitic rocks that intruded the undifferentiated basement. Thirty (30) representative muscovite extracts from the pegmatite samples were analysed for major-trace and rare earth elements using Inductively Coupled Atomic Emission Spectrornetry (ICP-AES).The chemical data shows that the rocks are siliceous with high SiO2 content(65.30 - 84.93%). CaO (0.11-0.35), MgO (0.17-0.41), and TiO, (0.0-0.85) values are generally low. Averages for Na2O and K2O are 2.87% and 1.87% respectively. The rocks are low in alkalis, indicating low to moderately high albitization, progressive rare alkali fractionation, and controlled Ta-Nb enrichment. Trace elements revealed Rb (1123.93 ppm), Ta (2016ppm), Be (88.6ppm), Ba (674.87ppm) and Nb (5150.8ppm).Elemental ratio for Rb/Sr (0.0066) and Mg/Li (0.00034) is low in certain.The enrichment variation plots of K/Rb versus Rb,Ta versus Rb, Ta against Nb, and Ta against Cs also revealed that have moderate to high Ta-Nb mineralization. Qualitative characterization of mineral phases is quartz, feldspar, biotite, mica,silica...